Which marketing method are most preferred by customers in BSN Wisma Maria: traditional marketing vs. modern marketing / Johari Shafiz Johan Ishaf - Johari Ishaf, Johari Shafiz (2017)
In this millennial age, many technology have been developed to enhance communication throughout the world. The new technology is able to reach a wider audience, and in lesser time. So does the marketing techniques that adopt the usage of the technology. Today, many organization has taken the opportunity to utilize the technology to perform a more effective marketing activity. BSN also did not miss in this utilization of technological medium. As the modem marketing took over the traditional method, does it imply to the success of a marketing activity? Thus, this study was conducted to identify the preference of marketing method for the Customer at BSN Wisma Maria. The purpose of this study is to compare which marketing method are are more preferred by customers at BSN Wisma Maria. The researcher is conducting quantitative method to obtain the need data. As much as 50 set of questionnaires was distributed to the customers of BSN Wisma Maria to be analyze and conclude which method are more preferable. The result of this study is to understand the preference of customer so that BSN can develop a more effective marketing strategies thus retain current customers and also attract new prospect in future.